Reversible electrospun fibers containing spiropyran for acid and base vapor sensing - Miguez, Flávio B.; Moreira, Olívia B. O.; de Oliveira, Marcone A. L.; Denadai, Ângelo M. L.; de Oliveira, Luiz F. C.; De Sousa, Frederico B. (Journal of materials research, 2023)
Among the various possible structural modifications spiropyrans may be subject to, ones containing alkyl sulfonates groups are commonly classified as photoacids. Both alkyl sulfonates spiropyrans named SON and SOH were structurally characterized and their acido- and photochromic properties were studied by UV–visible spectroscopy. Electrospun poly-ε-caprolactone (PCL) fibers were obtained, in which SON or SOH were incorporated with the goal of detecting acid and base vapors. PCL fibers containing the derivatives SON and SOH were successfully obtained (0.8 μm range), capable of acting as colorimetric vapor sensors according to the acidochromic properties of the spiropyrans. PCL-SON fibers presented quick vapor sensing capability, with colorimetric change within 10 s of exposure. Scanning electronic microscopy was crucial to characterize the morphology of these fibers before and after being used in the sensing process. This material could be reversibly reutilized in the sensing of acids and bases vapors according to the results presented. Graphical abstract Macroscopic color change for electrospun fibers based on acid or base vapors